2022
DOI: 10.1108/jtf-01-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Transformational marketing and transformational travel

Abstract: PurposeThis research seeks to understand if transformational marketing can be used as a tool that helps destinations to create products that can be individually, or group tailored to result in an enjoyable way to gain self-awareness, spiritual experience and an expansion of consciousness.Design/methodology/approachThis article is exploratory and with it, one intended to raise questions and hypotheses aiming to broaden the discussion scope on transformational marketing as a tool to create products that can not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Considering the historical approach of testing ideas and concepts through the "trial and error" principle, it is suggested that initial action in aligning the findings of this study would involve the proposition of an implementation framework for transformative cycling experiences within a designated region, followed by the evaluation of its execution. This framework can be devised by either integrating and emphasising transformative elements, such as self-reflection and personal growth, into the cycling landscape or advancing it even more by drawing insights from established theories, including Mezirow's transformative learning theory [30], the famous Campbell's Hero's Journey [29], and other relevant frameworks such as the model for designing tourism experiences for inner transformation of the individuals [24], strategy framework for tourism practitioners [133] tourist transformation model [134], model of TT learning [135], transformative leadership [122], retrieving ideas about transformational tourism marketing [136] or even following the lines of tourists' personality change scale after experiencing transformative travel experiences [137].…”
Section: Transformative Experiences In Ctmentioning
confidence: 99%
“…Considering the historical approach of testing ideas and concepts through the "trial and error" principle, it is suggested that initial action in aligning the findings of this study would involve the proposition of an implementation framework for transformative cycling experiences within a designated region, followed by the evaluation of its execution. This framework can be devised by either integrating and emphasising transformative elements, such as self-reflection and personal growth, into the cycling landscape or advancing it even more by drawing insights from established theories, including Mezirow's transformative learning theory [30], the famous Campbell's Hero's Journey [29], and other relevant frameworks such as the model for designing tourism experiences for inner transformation of the individuals [24], strategy framework for tourism practitioners [133] tourist transformation model [134], model of TT learning [135], transformative leadership [122], retrieving ideas about transformational tourism marketing [136] or even following the lines of tourists' personality change scale after experiencing transformative travel experiences [137].…”
Section: Transformative Experiences In Ctmentioning
confidence: 99%